Acquisition and optimization of the operating data in absorption refrigeration system - Yan, Soo Ling (2015)
Conventional air conditioning unit are commonly used in today’s household and offices. They required high power consumption and hence contribute to the high cost of electricity bill. Many researches have being done on absorption refrigeration system as it provides an alternative to these issues. In absorption refrigeration systems, the absorber is a critical component of absorption cycles which is widely recognized as the bottle neck, with its performance directly affecting the size, efficiency and cost of the system. The absorber is a vital component of absorption cycles in absorption refrigeration systems. It is commonly recognized as the bottle neck, with its performance having a direct effect on size efficiency and cost of the system. The report focuses on the understanding of the working principle, evaluating the available absorber type in the market and selecting a specific absorber to have a better overall performance of the system. The challenge in this projected will be reviewed for the absorption refrigeration system. Recommendation for future work is suggested.